EDUCATION AND IMPLEMENTATION OF SOLAR-POWERED ELECTRIC SPRAYERS FOR FARMERS TO SUPPORT RENEWABLE ENERGY IN PETUK LITI VILLAGE - Lola Cassiophea; Tarita Aprilani Sitinjak; Revianti Coenraad; Whendy Trissan; Wiratno Y Sigin; Topan Eka Putra; Tuah; Danar A.W Gautama; Ni Putu Diah Agustin Permanasuri; Mega Kurniawati; Petrisly Perkasa; Pitro; Nor Hikmah Wati (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2025)
Geographically, Petuk Liti Village is located within Pulang Pisau Regency and within the Kahayan Tengah District. This village also serves as a transportation hub between regencies, including Gunung Mas Regency, South Barito Regency, North Barito Regency, and Kapuas Regency. In agriculture, plantations, and fisheries, the residents of Petuk Liti Village primarily cultivate rubber, oil palm, and rattan trees. Manual spraying is still often carried out using conventional tools such as knapsack sprayers, which are manually operated or powered by fossil fuel engines. Besides being tiring, using these tools is inefficient in terms of time and energy, and contributes to carbon emissions that worsen environmental conditions (Putri & Santoso, 2020). With the increasing need for energy-efficient and environmentally friendly technology, an innovative solution is needed, namely the implementation of solar panel-based electric sprayers. Through an educational and applied approach, this community service is expected to improve farmers' skills and awareness of the importance of transitioning to green energy in daily agricultural production activities. The targeted outputs of this community service are the manufacture of electric sprayers and the publication of articles in SINTA-accredited journals and HKI.